Internationale Personalwirtschaft und Internationales Arbeitsrecht

Preprocessed Global Visibility for Real-Time Rendering on Low-End Hardware - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias (Advances in Visual Computing)
We present an approach for real-time rendering of complex 3D scenes consisting of millions of polygons on limited graphics hardware. In a preprocessing step, powerful hardware is used to gain fine granular global visibility information of a scene using an adaptive sampling algorithm. Additively the visual influence of each object on the eventual rendered image is estimated. This influence is used to select the most important objects to display in our approximative culling algorithm. After the visibility data is compressed to meet the storage capabilities of small devices, we achieve an interactive walkthrough of the Power Plant scene on a standard netbook with an integrated graphics chipset.

Continuous and Discrete Concepts for Detecting Transport Barriers in the Planar Circular Restricted Three Body Problem - Dellnitz, Michael; Padberg, Kathrin; Preis, Robert; Thiere, Bianca (Nonlinear Science and Complexity)

Solving optimal control problems by using inherent dynamical properties - Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Kobilarov, Marin (PAMM)

Spacecraft trajectories to the L3 point of the Sun–Earth three-body problem - Tantardini, Marco; Fantino, Elena; Ren, Yuan; Pergola, Pierpaolo; Gómez, Gerard; Masdemont, Josep J. (Celestial Mechanics and Dynamical Astronomy)

Detecting Initial Guesses for Trajectories in the (P)CRTBP - Thiere, Bianca; Ober-Blöbaum, Sina; Pergola, Pierpaolo (AIAA/AAS Astrodynamics Specialist Conference)

Das Gendiagnostikgesetz - Krimphove, Dieter (Arbeit und Arbeitsrecht (AuA))

Im Überblick: Die Beteiligungsrechte des Betriebsrats - Krimphove, Dieter (Der Betriebsrat)

Brauchen wir die Europäische Genossenschaft? - Krimphove, Dieter (EuZW)

Computergestützte traumatherapeutische Behandlungsmöglichkeiten bei Verkehrsunfallopfern von Kindern und Jugendlichen - Huck, Wilfried; Alakbarov, Alexej; Domik, Gitta; Radkowski, Rafael; Tölke, Roswitha; Mikus, Ann-Cathrin; Geisen, Silke (12. Jahrestagung der Deutschsprachigen Gesellschaft für Psychotraumatologie (DeGPT))

Edoardo Ferrante: Consensualismo e Trascrizione, Cedam Padova, 2008, pp I-XIV; 1-367 - Krimphove, Dieter (Rivista Trimesttriale di Diritto e Procedura Civile Anno LXIV Fasc.)

Preisfindung für hybride Leistungsbündel--Modellbasierte Integration von Ansätzen zur Entscheidungsunterstützung - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Dienstleistungsmodellierung 2010)

Online-Produktkonfiguratoren – Status quo und Entwicklungsperspektiven - Becker, Jörg; Knackstedt, Ralf; Müller, Oliver; Benölken, Alexander; Schmitt, Oliver; Thillainathan, Mayooran; Schulke, André (Vertriebsinformationssysteme)

An ontology-based natural language service discovery engine--design and experimental evaluation - Becker, Jörg; Müller, Oliver; Woditsch, Manuel (European Conference on Information Systems)

Proof-Carrying Hardware: Concept and Prototype Tool Flow for Online Verification - Drzevitzky, Stephanie; Kastens, Uwe; Platzner, Marco (International Journal of Reconfigurable Computing)

Virtuelle Speicherverwaltung für Hardware Threads in Rekonfigurierbaren Systemen - Agne, Andreas

EMG-basierte Ganganalyse - Boschmann, Alexander

Evolvable Cache Controller - Breitlauch, Daniel

Soft Microprocessors with tightly coupled Application-Specific Coprocessors - Dridger, Denis

Parallelization of the UCT Algorithm on HPC-Clusters - Graf, Tobias

Testdatenkompression mit Hilfe der Netzwerkinfrastruktur - Fröse, Viktor; Ibers, Rüdiger; Hellebrand, Sybille
Keywords: WORKSHOP

Fluctuating EMG Signals: Investigating Long-term Effects of Pattern Matching Algorithms - Kaufmann, Paul; Englehart, Kevin; Platzner, Marco (International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC))

A Novel Hybrid Evolutionary Strategy and its Periodization with Multi-objective Genetic Optimizers - Kaufmann, Paul; Knieper, Tobias; Platzner, Marco (IEEE World Congress on Computational Intelligence (WCCI), Congress on Evolutionary Computation (CEC))

Selected papers from the 18th International Conference on Field Programmable Logic and Applications, FPL 2008 (editorial) - Kebschull, Udo; Platzner, Marco; Teich, Jürgen (IET Computers Digital Techniques)

Hybridization of Global Multi-Objective and Local Search Techniques - Knieper, Tobias

Coping with Resource Fluctuations: The Run-time Reconfigurable Functional Unit Row Classifier Architecture - Knieper, Tobias; Kaufmann, Paul; Glette, Kyrre; Platzner, Marco; Torresen, Jim (IEEE Intl. Conf. on Evolvable Systems (ICES))

ReconOS: An Operating System for Dynamically Reconfigurable Hardware - Lübbers, Enno; Platzner, Marco (Dynamically Reconfigurable Systems: Architectures, Design Methods and Applications)

FPGA/CPU Multicore-Plattform für ReconOS/eCos - Meiche, Robert

Transparente Hardwarebeschleunigung durch Shared Library Interposing - Niekamp, Manuel

A Token-Ring Network-On-Chip for Message Passing in ReconOS - Runde, Bodo

Scheduling Support for Heterogeneous Hardware Accelerators under Linux - Wiersema, Tobias

Dynamically Reconfigurable Systems: Architectures, Design Methods and Applications

Sub-threshold charge recovery circuits - Khatir, Mehrdad; Ghasemzadeh Mohammadi, Hassan; Ejlali, Alireza (Computer Design (ICCD), 2010 IEEE International Conference on)

Barometric height estimation combined with map-matching in a loosely-coupled Kalman-filter - Bevermeier, Maik; Walter, Oliver; Peschke, Sven; Haeb-Umbach, Reinhold (7th Workshop on Positioning Navigation and Communication (WPNC 2010))
In this paper we present a robust location estimation algorithm especially focused on the accuracy in vertical position. A loosely-coupled error state space Kalman filter, which fuses sensor data of an Inertial Measurement Unit and the output of a Global Positioning System device, is augmented by height information from an altitude measurement unit. This unit consists of a barometric altimeter whose output is fused with topographic map information by a Kalman filter to provide robust information about the current vertical user position. These data replace the less reliable vertical position information provided the GPS device. It is shown that typical barometric errors like thermal divergences and fluctuations in the pressure due to changing weather conditions can be compensated by the topographic map information and the barometric error Kalman filter. The resulting height information is shown not only to be more reliable than height information provided by GPS. It also turns out that it leads to better attitude and thus better overall localization estimation accuracy due to the coupling of spatial orientations via the Direct Cosine Matrix. Results are presented both for artificially generated and field test data, where the user is moving by car.
Keywords: altitude measurement unit; barometers; barometric altimeter; barometric error Kalman filter; barometric height estimation; direct cosine matrix; global positioning system; Global Positioning System; GPS device; height information; height measurement; inertial measurement unit; Kalman filters; loosely-coupled error state space Kalman filter; loosely-coupled Kalman-filter; map matching; robust information; robust location estimation; sensor fusion; topographic map information; vertical user position

Model-Based Feature Enhancement for Reverberant Speech Recognition - Krueger, Alexander; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In this paper, we present a new technique for automatic speech recognition (ASR) in reverberant environments. Our approach is aimed at the enhancement of the logarithmic Mel power spectrum, which is computed at an intermediate stage to obtain the widely used Mel frequency cepstral coefficients (MFCCs). Given the reverberant logarithmic Mel power spectral coefficients (LMPSCs), a minimum mean square error estimate of the clean LMPSCs is computed by carrying out Bayesian inference. We employ switching linear dynamical models as an a priori model for the dynamics of the clean LMPSCs. Further, we derive a stochastic observation model which relates the clean to the reverberant LMPSCs through a simplified model of the room impulse response (RIR). This model requires only two parameters, namely RIR energy and reverberation time, which can be estimated from the captured microphone signal. The performance of the proposed enhancement technique is studied on the AURORA5 database and compared to that of constrained maximum-likelihood linear regression (CMLLR). It is shown by experimental results that our approach significantly outperforms CMLLR and that up to 80% of the errors caused by the reverberation are recovered. In addition to the fact that the approach is compatible with the standard MFCC feature vectors, it leaves the ASR back-end unchanged. It is of moderate computational complexity and suitable for real time applications.
Keywords: ASR; AURORA5 database; automatic speech recognition; Bayesian inference; belief networks; CMLLR; computational complexity; constrained maximum likelihood linear regression; least mean squares methods; LMPSC computation; logarithmic Mel power spectrum; maximum likelihood estimation; Mel frequency cepstral coefficients; MFCC feature vectors; microphone signal; minimum mean square error estimation; model-based feature enhancement; regression analysis; reverberant speech recognition; reverberation; RIR energy; room impulse response; speech recognition; stochastic observation model; stochastic processes

Options for Modelling Temporal Statistical Dependencies in an Acoustic Model for ASR - Leutnant, Volker; Haeb-Umbach, Reinhold (36. Deutsche Jahrestagung fuer Akustik (DAGA 2010))
Traditionally, ASR systems are based on hidden Markov models with Gaussian mixtures modelling the state-conditioned feature distribution. The inherent assumption of conditional independence, stating that a feature's likelihood solely depends on the current HMM state, makes the search computationally tractable, nevertheless has also been identified to be a major reason for the lack of robustness of such systems. Linear dynamic models have been proposed to overcome this weakness by employing a hidden dynamic state process underlying the observed features. Though performance of linear dynamic models on continuous speech/phone recognition tasks has been shown to be superior to that of equivalent static models, this approach still cannot compete with the established acoustic models. In this paper we consider the combination of hidden Markov models based on Gaussian mixture densities (GMM-HMMs) and linear dynamic models (LDMs) as the acoustic model for automatic speech recognition systems. In doing so, the individual strengths of both models, i.e. the modelling of long-term temporal dependencies by the GMM-HMM and the direct modelling of statistical dependencies between consecutive feature vectors by the LDM, are exploited. Phone classification experiments conducted on the TIMIT database indicate the prospective use of this approach for the application to continuous speech recognition.

On the Exploitation of Hidden Markov Models and Linear Dynamic Models in a Hybrid Decoder Architecture for Continuous Speech Recognition - Leutnant, Volker; Haeb-Umbach, Reinhold (Interspeech 2010)
Linear dynamic models (LDMs) have been shown to be a viable alternative to hidden Markov models (HMMs) on small-vocabulary recognition tasks, such as phone classification. In this paper we investigate various statistical model combination approaches for a hybrid HMM-LDM recognizer, resulting in a phone classification performance that outperforms the best individual classifier. Further, we report on continuous speech recognition experiments on the AURORA4 corpus, where the model combination is carried out on wordgraph rescoring. While the hybrid system improves the HMM system in the case of monophone HMMs, the performance of the triphone HMM model could not be improved by monophone LDMs, asking for the need to introduce context-dependency also in the LDM model inventory.

Ungrounded Independent Non-Negative Factor Analysis - Raj, Bhiksha; Wilson, Kevin W.; Krueger, Alexander; Haeb-Umbach, Reinhold (Interspeech 2010)
We describe an algorithm that performs regularized non-negative matrix factorization (NMF) to find independent components in non-negative data. Previous techniques proposed for this purpose require the data to be grounded, with support that goes down to 0 along each dimension. In our work, this requirement is eliminated. Based on it, we present a technique to find a low-dimensional decomposition of spectrograms by casting it as a problem of discovering independent non-negative components from it. The algorithm itself is implemented as regularized non-negative matrix factorization (NMF). Unlike other ICA algorithms, this algorithm computes the mixing matrix rather than an unmixing matrix. This algorithm provides a better decomposition than standard NMF when the underlying sources are independent. It makes better use of additional observation streams than previous non-negative ICA algorithms.

An EM Approach to Integrated Multichannel Speech Separation and Noise Suppression - Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (International Workshop on Acoustic Echo and Noise Control (IWAENC 2010))
In this contribution we provide a unified treatment of blind source separation (BSS) and noise suppression, two tasks which have traditionally been considered different and for which quite different techniques have been developed. Exploiting the sparseness of the sources in the short time frequency domain and using a probabilistic model which accounts for the presence of additive noise and which captures the spatial information of the multi-channel recording, a speech enhancement system is developed which suppresses noise and simultaneously separates speakers in case multiple speakers are active. Source activity estimation and model parameter estimation form the E-step and the M-step of the Expectation Maximization algorithm, respectively. Experimental results obtained on the dataset of the Signal Separation Evaluation Campaign 2010 demonstrate the effectiveness of the proposed system.

Blind speech separation employing directional statistics in an Expectation Maximization framework - Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2010))
In this paper we propose to employ directional statistics in a complex vector space to approach the problem of blind speech separation in the presence of spatially correlated noise. We interpret the values of the short time Fourier transform of the microphone signals to be draws from a mixture of complex Watson distributions, a probabilistic model which naturally accounts for spatial aliasing. The parameters of the density are related to the a priori source probabilities, the power of the sources and the transfer function ratios from sources to sensors. Estimation formulas are derived for these parameters by employing the Expectation Maximization (EM) algorithm. The E-step corresponds to the estimation of the source presence probabilities for each time-frequency bin, while the M-step leads to a maximum signal-to-noise ratio (MaxSNR) beamformer in the presence of uncertainty about the source activity. Experimental results are reported for an implementation in a generalized sidelobe canceller (GSC) like spatial beamforming configuration for 3 speech sources with significant coherent noise in reverberant environments, demonstrating the usefulness of the novel modeling framework.
Keywords: array signal processing; blind source separation; blind speech separation; complex vector space; complex Watson distribution; directional statistics; expectation-maximisation algorithm; expectation maximization algorithm; Fourier transform; Fourier transforms; generalized sidelobe canceller; interference suppression; maximum signal-to-noise ratio beamformer; microphone signal; probabilistic model; spatial aliasing; spatial beamforming configuration; speech enhancement; statistical distributions

On the Impact of Human Driver Behavior on Intelligent Transportation Systems - Dressler, Falko; Sommer, Christoph (2010 IEEE 71st Vehicular Technology Conference)

Emissions vs. Travel Time: Simulative Evaluation of the Environmental Impact of ITS - Sommer, Christoph; Krul, Robert; German, Reinhard; Dressler, Falko (2010 IEEE 71st Vehicular Technology Conference)

On the feasibility of UMTS-based Traffic Information Systems - Sommer, Christoph; Schmidt, Armin; Chen, Yi; German, Reinhard; Koch, Wolfgang; Dressler, Falko (Ad Hoc Networks)

Improving the Accuracy of IVC Simulation Using Crowd-sourced Geodata - Sommer, Christoph; Eckhoff, David; Dressler, Falko (PIK - Praxis der Informationsverarbeitung und Kommunikation)

Die digitale Edition von Webers Klarinettenquintett – Ein Vergleich der Edirom-Versionen 2004 und 2008 - Röwenstrunk, Daniel (Digitale Edition zwischen Experiment und Standardisierung)

Massive Statistical Process Variations - A Grand Challenge for Testing Nanoelectronic Circuits - Becker, Bernd; Hellebrand, Sybille; Polian, Ilia; Straube, Bernd; Vermeiren, Wolfgang; Wunderlich, Hans-Joachim (40th Annual IEEE/IFIP International Conference on Dependable Systems and Networks Workshops (DSN-W'10))

An Analysis of the FURIA algorithm for fuzzy rule induction - Hüllermeier, Eyke; Hühn, J. (Advances in Machine Learning I: Dedicated to the Memory of Professor Ryszard S.Michalski)

Preference Learning: An Introduction - Fürnkranz, J.; Hüllermeier, Eyke (Preference Learning)

BlueJ Visual Debugger for Learning the Execution of Object-Oriented Programs? - Bennedsen, Jens; Schulte, Carsten (TOCE)

Comparison of OOP first and OOP later: first results regarding the role of comfort level - Ehlert, Albrecht; Schulte, Carsten (ITiCSE)

10th Koli Calling International Conference on Computing Education Research, Koli Calling '10, Koli, Finland, October 28-31, 2010

Didaktik der Informatik - Möglichkeiten empirischer Forschungsmethoden und Perspektiven der Fachdidaktik. 6. Workshop der GI-Fachgruppe "Didaktik der Informatik", 16. - 17. September 2010 in Oldenburg

Efficient similarity retrieval for protein binding sites based on histogram comparison - Fober, T.; Mernberger, M.; Klebe, G.; Hüllermeier, Eyke (In Proceedings GCB-2010 German Conference on Bioinformatics Braunschweig, Germany)

On label dependence in multi-label classification - Dembczynski, K.; Waegeman, W.; Cheng, W.; Hüllermeier, Eyke (In Proceedings MLD-2010, 2nd International Workshop on Learning from Multi-Label Data, Haifa, Israel)

Dynamics of photoexcitation and stimulated optical emission in conjugated polymers: A multiscale quantum-chemistry and Maxwell-Bloch-equations approach - Schumacher, Stefan; Galbraith, Ian; Ruseckas, Arvydas; Turnbull, Graham A.; Samuel, Ifor D. W. (Physical Review B)

Streaming-Based Verification of XML Signatures in SOAP Messages - Somorovsky, Juraj; Jensen, Meiko; Schwenk, Jörg (2010 6th World Congress on Services)

An improved mode-tracing algorithm to compute dispersion curves of acoustic waveguides - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Semi-analytical approaches for the description of dispersion in acoustic waveguides are based on root finding in a characteristic function. A mode-tracing algorithm helps to find all solutions of this problem by consecutively bracketing single roots. In this contribution we present a multistage and adaptive mode-tracing algorithm, which uses an adaptive step size for the prediction of consecutive solutions as well as an adaptive estimation of the search space around these predictions. Furthermore we present a validation stage to ensure the correlation between consecutive solutions alias waveguide modes.

Entwicklung und Parametrisierung eines Mode-Tracing Algorithmus für halbanalytische Solver - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Die computergestützte Simulation geführter elastischer Wellen in ein- oder mehrschichtigen Wellenleitern ist in vielen Bereichen der akustischen Forschung ein essentielles Modellierungswerkzeug. Sie ermöglicht, auch in komplexen Systemen, eine Beschreibung der Wellenausbreitungsvorgänge, deren analytische Lösung zu aufwendig oder nicht durchführbar ist. Im ersten Abschnitt dieses Beitrags wird auf den halbanalytischen Solver bzw. die mathematische Formulierung des die Wellenausbreitung beschreibenden Problems eingegangen. Der zweite Abschnitt beinhaltet den mehrstufigen Aufbau eines Tracing-Algorithmus, welcher den Lösungsraum des Solvers adaptiv einschränkt, so dass Leistungsfähigkeit und Robustheit des Gesamtalgorithmus gestärkt werden.

Improved system identification for simultaneous transmitting and receiving in single transducer applications - Schröder, Andreas; Henning, Bernd
In single transducer applications it would be desirable if the received electrical signal (echo signal) could be evaluated during transmitting. Thereby it is possible to measure very short distances. There are some solutions to realize this, but they have one limitation which prevents the usage in many industrial application. They need a calibration without an echo. The main problem is that this calibration has to be repeated whenever the process parameters like temperature or acoustic load change. This contribution presents an approach which uses a model identification based on different successive measurements which may include echoes. It is done by an impulse response decomposition followed by a principle component analysis. Results of measurements with sine burst excitation and a reflector in front of the transducer are presented.

Interfaceschaltung für einen simultanen Sende- und Empfangsbetrieb mit einem einzelnen Ultraschallwandler - Schröder, Andreas; Henning, Bernd
In der Ultraschallmesstechnik (Abstandsmessung, NDT) ist es zur Detektion naheliegender Reflektoren bzw. zur Erfassung der Medienrückwirkung (Wirkung der akustischen Last) notwendig, die Empfangssignale auszuwerten, noch während der Schallwandler mit dem Sendesignal angesteuert wird oder die Sendesignalenergie am Schallwandler noch nicht ausreichend abgeklungen ist. In diesem Beitrag wird eine Schaltung zur Kompensation des Sendesignals beschrieben, welche die unmittelbare Auswertung des Empfangssignals ermöglicht.

Messrohr für einen Ultraschall-Durchflussmesser und Ultraschall Durchflussmesser - Schröder, Andreas; Rautenberg, Jens; Behlen, H.; Ziegler, Horst; Unverzagt, Carsten; Gaugler, Ulrich; Glatter, T.; Horrn, R.; Kroemer, H.; Schmidt-Schoenian, Axel; Sonnenberg, Hans-Michael; Henning, Bernd

Weniger Sehen-mehr Verstehen: Größen-basierte und Textur-basierte Transferfunktionen zur Volumenvisualisierung von CT Daten der Koronargefäße - Arens, Stephan; Domik, Gitta; Weise, Rainer; Fricke, Harald; Burchert, Wolfgang (Tagungsband der Deutschen Gesellschaft für physikalische Medizin)

Extending the corkscrew algorithm to find bifurcations of vessels - Wette, Philip; Arens, Stephan; Elsner, Andreas; Domik, Gitta (Computer Graphics and Imaging)

Visual representations for supporting an ontology-based semantic navigation of medical volume data - Peters, Sebastian; Kelm, Michael; Huber, Martin; Seifert, Sascha; Elsner, Andreas; Domik, Gitta (Proceedings of the 11th IASTED International Conference)

Similarity measures for protein structures based on fuzzy histogram comparison - Fober, T.; Hüllermeier, Eyke (in Proceedings WCCI-2010, World Congress on Computational Intelligence, Barcelona, Spain)

Pattern trees for regression and fuzzy systems modeling - Senge, Robin; Hüllermeier, Eyke (in Proceedings WCCI-2010, World Congress on Computational Intelligence, Barcelona, Spain)

Queryable SEPA Message Compression by XML Schema Subtraction - Böttcher, Stefan; Hartel, Rita; Messinger, Christian (ICEIS 2010 - Proceedings of the 12th International Conference on Enterprise Information Systems)

CluX - Clustering XML Sub-trees - Böttcher, Stefan; Hartel, Rita; Krislin, Christoph (ICEIS 2010 - Proceedings of the 12th International Conference on Enterprise Information Systems)

Using XML Schema Subtraction to Compress Electronic Payment Messages - Böttcher, Stefan; Hartel, Rita; Messinger, Christian (Enterprise Information Systems - 12th International Conference, ICEIS 2010, Revised Selected Papers)

Searchable Compression of Office Documents by XML Schema Subtraction - Böttcher, Stefan; Hartel, Rita; Messinger, Christian (Database and XML Technologies - 7th International XML Database Symposium, XSym 2010)

Höchstfeste Multimaterialsysteme aus Stahl und Faserverbundkunststoffen - Lauter, Christian; Tröster, Thomas; Sköck-Hartmann, Britta; Gries, Thomas; Linke, Marcus (VDI Konstruktion: Ingenieur-Werkstoffe)

GARLig: A fully automated tool for subset selection of large fragment spaces via a self-adaptive genetic algorithm - Pfeffer, P.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (Journal of Chemical Information and Modeling)

Combining predictions in pairwise classification: An optimal adaptive voting strategy and its relation to weighted voting - Hüllermeier, Eyke; Vanderlooy, S. (Pattern Recognition)

On predictive accuracy and risk minimization in pairwise label ranking - Hüllermeier, Eyke; Fürnkranz, J. (Journal of Computer and System Sciences)

Europarecht inklusive CD-ROM mit Gesetzen, Urteilen, Hörfassung und interaktiven Falllösungen - Krimphove, Dieter

Handelsrecht - mit Grundzügen des Wechsel- und Scheckrechts (Gesetze, Urteile, Fälle und Lösungen, Sprachfassung auf interaktiver CD) - Krimphove, Dieter

A Continuous, Local Strategy for Constructing a Short Chain of Mobile Robots - Degener, Bastian; Kempkes, Barbara; Kling, Peter; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

A local O(n2) gathering algorithm - Degener, Bastian; Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Proceedings of the 22nd ACM symposium on Parallelism in algorithms and architectures - SPAA '10)

Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part II.

Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part I.

Evaluation of cost functions for FEA based transducer optimization - Schröder, Andreas; Rautenberg, Jens; Henning, Bernd (Physics Procedia)

A new method of spatial filtering for Schlieren visualization of ultrasound wave fields - Unverzagt, Carsten; Olfert, Sergei; Henning, Bernd (Physics Procedia)

PC gestützte Entwicklung von Ultraschallsensoren - Henning, Bernd

Adaptives Mode-Tracing und numerische Stabilisierung modellierter Anregungsstrukturen für die halbanalytische Simulation geführter Wellen - Bause, Fabian; Henning, Bernd

Halbanalytische Modellierung akustischer Wellenausbreitung im ein- und mehrschichtigen Wellenleiter - Bause, Fabian

Effizientes Ultraschalltransducerdesign und Methoden zur akustischen Materialdatenbestimmung - Henning, Bernd

Ausbeute und Fehlertoleranz bei dreifach modularer Redundanz - Hunger, Marc; Hellebrand, Sybille (4. GMM/GI/ITG-Fachtagung "Zuverlässigkeit und Entwurf")

Nano-Electronic Systems - Hellebrand, Sybille

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part II: Circumferential variation of the wall superheat for a horizontal 25mm copper cylinder - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)

Nucleate pool boiling, film boiling and single-phase free convection at pressures up to the critical state. Part I: Integral heat transfer for horizontal copper cylinders - Gorenflo, Dieter; Baumhögger, Elmar; Windmann, Thorsten; Herres, Gerhard (International Journal of Refrigeration)

The Use of Instant Messaging in Working Relationship Development: A Case Study - Cho, Hee-Kyung; Trier, Matthias; Kim, Eunhee (Journal of Computer-Mediated Communication)

Struktur und Dynamik in der Netzwerkanalyse - Trier, Matthias (Handbuch Netzwerkforschung)

Towards a Systematic Approach for Capturing Knowledge-Intensive Business Processes - Trier, Matthias; Müller, Claudia (Practical Aspects of Knowledge Management)

Analyzing the Dynamics of Community Formation Using Brokering Activities - Trier, Matthias; Bobrik, Annette (Communities and Technologies 2007)

Network coding in passive optical networks - Miller, Konstantin; Biermann, Thorsten; Woesner, Hagen; Karl, Holger (Network Coding (NetCod), 2010 IEEE International Symposium on)

Tutte's 5-flow conjecture for cyclically highly connected cubic graphs - Steffen, Eckhard (Discrete Mathematics)

Bricks and conjectures of Berge, Fulkerson and Seymour - Mkrtchyan, Vahan; Steffen, Eckhard (arXiv:1003.5782)
An $r$-graph is an $r$-regular graph where every odd set of vertices is connected by at least $r$ edges to the rest of the graph. Seymour conjectured that any $r$-graph is $r+1$-edge-colorable, and also that any $r$-graph contains $2r$ perfect matchings such that each edge belongs to two of them. We show that the minimum counter-example to either of these conjectures is a brick. Furthermore we disprove a variant of a conjecture of Fan, Raspaud.

RiaS: overlay topology creation on a PlanetLab infrastructure - Lischka, Jens; Karl, Holger (Proceedings of the second ACM SIGCOMM workshop on Virtualized infrastructure systems and architectures)

Energy efficiency model of network-coded cooperation in wireless sensor networks - Woldegebreal, Dereje H; Karl, Holger (Sensor Technologies and Applications (SENSORCOMM), 2010 Fourth International Conference on)

Cooperative communication to improve reliability and efficient neighborhood wakeup in wireless sensor networks - Khan, Rana Azeem M; Karl, Holger (Proceedings of the Fourth International Conference on Mobile Ubiquitous Computing (UBICOMM 2010))